Semiconducting organic polymers as hole-transport layer in solid-state dye sensitized solar cells: Comprehensive insights from femtosecond transient spectroscopy and device optimization - Kumar, R; Grancini, G; Petrozza, A; Snaith, H; Lanzani, G (2012)
Device optimization and ultrafast absorption spectroscopic investigations on the role of semiconducting polymer as hole-transport layer in solid-state dye sensitized solar cells suggest their dual role of dye-regeneration and light-antenna assisting in improved photoconversion-efficiencies. © 2012 OSA.